Inhibition of Spleen Tyrosine Kinase Potentiates Paclitaxel-Induced Cytotoxicity in Ovarian Cancer Cells by Stabilizing Microtubules - Yu, Yu; Gaillard, S.; Phillip, J.; Huang, T.; Pinto, S.; Tessarollo, N.; Zhang, Z.; Pandey, A.; Wirtz, D.; Ayhan, A.; Davidson, B.; Wang, T.; et al. (2015)
Resistance to chemotherapy represents a major obstacle for long-term remission, and effective strategies toovercome drug resistance would have significant clinical impact. We report that recurrent ovarian carcinomas after paclitaxel/carboplatin treatment have higher levels of spleen tyrosine kinase (SYK) and phospho-SYK. Invitro, paclitaxel-resistant cells expressed higher SYK, and the ratio of phospho-SYK/SYK positively associated with paclitaxel resistance in ovarian cancer cells. Inactivation of SYK by inhibitors or gene knockdown sensitized paclitaxel cytotoxicity invitro and invivo. Analysis of the phosphotyrosine proteome in paclitaxel-resistant tumor cells revealed that SYK phosphorylates tubulins and microtubule-associated proteins. Inhibition of SYK enhanced microtubule stability in paclitaxel-resistant tumor cells that were otherwise insensitive. Thus, targeting SYK pathway is a promising strategy to enhance paclitaxel response.